New York inmates' HIV risk behaviors: the implications for prevention policy and programs. - Mahon, N (1996)
OBJECTIVES: The median incidence rate of acquired immunodeficiency syndrome (AIDS) among prisoners is 7 times higher than for the general population. Yet high-risk sexual activity and drug use in US correctional facilities remain unexamined. This study explores inmate perceptions of high-risk behavior in New York state prisons and New York City jails and seeks to generate hypotheses to inform policies and future research. METHODS: Participants were 22 former New York state prisoners and 28 current New York City inmates. Participants attended one of six focus groups and completed an anonymous questionnaire. Audiotapes of the groups were transcribed and evaluated. RESULTS: A range of consensual and nonconsensual sexual activity occurs among inmates and between inmates and staff. Without official access to latex barriers, prisoners use ineffective makeshift devices, like rubber gloves and used plastic wrap, in attempts to practice safer sex. Prisoners also shoot drugs intravenously with used syringes and pieces of pens and light bulbs. CONCLUSIONS: The absence of harm-reduction devices behind bars may create a greater risk of HIV transmission there than in the community. Officials should consider distributing risk-reduction devices to prisoners through anonymous methods.